Модель "затухающего" конфликта - Казаков, В. (Социология: теория, методы, маркетинг, 2001)
The article is devoted to the model of a fading conflict contrasted to an escalating one. The mechanisms of a fading conflict development are considered, along with its subjects, the functions of the sides involved, theri aing and motivations. The fading conflict institutialization is interpreted as a prevequisite of its settling by means of a compromise.